2019
DOI: 10.1038/s41467-018-08145-2
|View full text |Cite
|
Sign up to set email alerts
|

A recurrent cancer-associated substitution in DNA polymerase ε produces a hyperactive enzyme

Abstract: Alterations in the exonuclease domain of DNA polymerase ε (Polε) cause ultramutated tumors. Severe mutator effects of the most common variant, Polε-P286R, modeled in yeast suggested that its pathogenicity involves yet unknown mechanisms beyond simple proofreading deficiency. We show that, despite producing a catastrophic amount of replication errors in vivo, the yeast Polε-P286R analog retains partial exonuclease activity and is more accurate than exonuclease-dead Polε. The major consequence of the arginine su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
103
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(114 citation statements)
references
References 54 publications
10
103
0
1
Order By: Relevance
“…However, V411 is far away from exonuclease active site may function by affecting the positions of other residues adjacent to the active site [9]. In yeast, POLE mutants with a weak exonuclease activity have more C>T and less C>A mutations than mutants with no exonuclease activity [7]. We therefore speculate that the proportionally reduced C>A and increased C>T mutation loads in V411 may arise due to stronger exonuclease activity, as the mutation is distal from that site.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…However, V411 is far away from exonuclease active site may function by affecting the positions of other residues adjacent to the active site [9]. In yeast, POLE mutants with a weak exonuclease activity have more C>T and less C>A mutations than mutants with no exonuclease activity [7]. We therefore speculate that the proportionally reduced C>A and increased C>T mutation loads in V411 may arise due to stronger exonuclease activity, as the mutation is distal from that site.…”
Section: Discussionmentioning
confidence: 92%
“…V411L and P286R are the two most frequent POLE mutants and they are located far away from each other in the exonuclease domain, thus conferring different functions [37]. Structural and molecular dynamics simulation studies in S. cerevisiae have revealed that P301R (P286R in Human) substitution prevents proper positioning of ssDNA in the exonuclease active site of Pol ε, resulting in promoting the extension of mismatched primer termini [7,8]. However, V411 is far away from exonuclease active site may function by affecting the positions of other residues adjacent to the active site [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Haploid yeast deficient in MMR and harboring pol3-D520V are not viable (41); therefore, we assessed the epistatic relationship between pol3-D520V and MMR deficiency in diploid strains, which can tolerate a higher level of mutagenesis. We used the MSH6 deletion to inactivate MMR as the Msh6-dependent pathway is primarily responsible for the repair of single-base mismatches (42), which is the predominant type of replication errors generated by exonucleasedeficient Polδ and Pole (43)(44)(45). Diploids homozygous for both pol3-D520V and msh6 mutations showed a strong synergistic increase in mutation rate as compared with the single pol3-D520V and msh6 mutants (SI Appendix, Table S2).…”
Section: Polδ Proofreads Errors Made By Pole But Pole Does Not Proofmentioning
confidence: 99%
“…POLE mutants with a weak exonuclease activity have more C>T and less C>A 280 mutations than mutants with no exonuclease activity (Xing et al, 2019). We therefore 281 speculate that the proportionally reduced C>A and increased C>T mutation loads in 282 V411 may arise due to stronger exonuclease activity, as the mutation is distal from 283 that site.…”
mentioning
confidence: 95%